Low temperature enzyme and method thereof - Raja Abdul Rahman, Raja Noor Zaliha (2009)
The present invention discloses manufacturing method of low temperature protease and special yeast strains, which can generate low temperature protease in the condition of low temperatures. More particularly, the present invention is to obtain a protease (preferably Cold-adapted protease PI12) using the marine strain of the Leucosporidium antarcticum sp.(NCYC accession no: 3391) for possible use in industries.